Análise multitemporal da fragilidade ambiental da bacia hidrográfica do córrego da Porteira no município de Aquidauana – MS - Nelson Oliveira da Cunha (2021)
The Córrego da Porteira watershed (BHCP) is located to the east of the urban perimeter of the city of Aquidauana – (MS), it has approximately 88,017 km² draining the Maracaju-Campo Grande Plateau where its main springs and its tributaries are located. In the last 53 years the Porteira stream has undergone significant changes in its landscape and has been suffering a siltation process mainly in its medium and low course as a result of the loss of soil within the limits of its basin, caused by natural phenomena influenced by anthropogenic actions due to the replacement of its autochthonous vegetation by exotic grasses for cattle feeding. This work aimed to perform a multitemporal analysis of the environmental fragility of the Porteira stream located in the city of Aquidauana – (MS), using remote sensing in a Geographic Information System (GIS) environment. The theoretical-methodological procedures were based on systemic and ecodynamic theories for empirical analysis of multitemporal environmental fragility and on digital image processing routines and spatial data processing in a GIS environment. The results show that from a natural point of view, there is a predominance of 44.29% of the area occupied by the middle class with potential fragility. Between 1966 and 2019, there was an increase in environmental fragility of 59.49%, evidenced by the low class of environmental fragility. It was found that the strong increase in the levels of environmental fragility translates into negative environmental impacts printed on the landscape over the period analyzed, which highlights the need for public policies for the recovery and prevention of environmental damage in BHCP.